Back to the roots? Critical reflections on the ‘root’ in Finno-Ugric linguistics - Johanna Laakso (Eesti ja Soome-ugri Keeleteaduse Ajakiri, 2017)
In Finno-Ugric linguistics, words are usually analyzed in terms of stems and affixes instead of abstract monosyllabic ‘roots’ in the Indo-European sense. However, there have been attempts to introduce the concept of ‘root’ alongside the historically disyllabic stems, in order to account for less regular connections between words and the non-canonic word formation mechanisms of the expressive vocabulary. Here, a few such attempts are critically analyzed in their historical and ideological contexts.